Drawing a Structural Model by the Most Effective Components on Optimal Global Marketing - Nazari, Farzad; Najafi, Soodabeh; Shahsavari, Farnaz; Zeynalzadeh, Aylar (Brazilian Journal of Operations & Production Management, 2020)
Goal: International trade and success in this field is one of the most important goals based on the profitability and reputation among different companies and organizations, in which the most important tool is optimal global and international marketing; therefore, this research aims at drawing the model of structure by the components influencing optimal global marketing. Design / Methodology / Approach: To this end, 385 experts, professionals, and scholars in this field, whose number was determined by the Cochran formula, completed a researcher-made questionnaire. In this paper used the structural equation method. Results: The results show that the application of technology, product quality, price, variety and communication (brand) are the five affecting factors on optimal global marketing. In the meantime, the product quality has the greatest effect on optimal global marketing, and with exception of the diversity which is the indirect predictor of optimal global marketing, other variables directly predict this indicator, as well as the results of fitting the model showed that the created model is an efficient and reliable tool for investigating the components affecting the identification of global optimal marketing. Practical implications: results of this study can be use to increase sales and supply rates of products Because by knowing the best marketing agents can increased the rate of supply of goods and products. Research limitations: This research has been done in Iran, Naturally, it has to be validated for use elsewhere in the world, it is possible that it may not be cited elsewhere or give different results. Originality / Value: It has not been studied so far and the results of this article can be used all over the world.